Water sorption and solubility of bulk-fill composites polymerized with a third generation LED LCU - Tuğba MİSİLLİ; Nihan GÖNÜLOL (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract The aim of this study was to compare the degree of water sorption and solubility in bulk-fills after curing with a polywave light source. A total of 120 disc-shaped specimens (8 mm diameter; 4 mm depth) were prepared from three regular bulk-fill materials (X-tra Fil, Tetric N-Ceram Bulk Fill, SonicFill), and a control material (Filtek Z250), cured in 3 different modes (standard: 1000 mW/cm2-20 s; high power: 1400 mW/cm2-12 s; xtra power: 3200 mW/cm2-6 s) using a third generation light-emitting diode light curing unit. Water sorption and solubility levels of the specimens were measured according to the ISO 4049:2009 specification after storing in distilled water for 30 days. Data were analyzed using two-way ANOVA and Tukey's post-hoc test (p < 0.05). The Z250 sample exposed to high power presented a higher sorption compared to the X-tra Fil and SonicFill samples. In xtra power mode, the values of Z250 and SonicFill were similar to each other and higher compared to those of X-tra Fil. Only SonicFill exhibited significantly different sorption values depending on the curing mode, the highest of which was achieved when using the xtra power mode. The highest solubility values were obtained for SonicFill. No statistically significant differences were found among other groups. No significant correlation was detected between water sorption and solubility. The traditional composite group exhibited a higher water sorption values than the bulk-fills. The reduction in polymerization time significantly increased the sorption of SonicFill. SonicFill showed the highest water solubility value among the composites tested.